Comparative Study of Pain on Injection of Propofol MCT-LCT with Propofol Nanoemulsion for General Anaesthesia - Shakya, Shailendra; Vaidya, Preeti; Paudel, Bibek (Journal of Nepalgunj Medical College, 2022)
Introduction: Pain during injection of propofol continues to be a major discomfort for patients. Different propofol formulations have been introduced to reduce the incidence of pain.Aims: To know the incidence, severity of pain at induction and post operative amnesic effect of two different formulations of propofol.Methods: This double-blinded comparative study involved randomly selected 100 patients undergoing elective surgery under general anesthesia with physical status score I or II (American Society of Anesthesiologists). Out of 100 patients, 50 received medium and long chain triglyceride Propofol (Group A) while another 50 received nanoemulsion Propofol (Group B) intravenously. Parameters measured and compared were the gender, age, weight, physical status score, pain on injection and postoperative recall of pain during injection of propofol.Results: Both groups were comparable with regards to age, gender, physical status score, mean duration of surgery. The presence of pain during injection with propofol in group A was 76% (38 patients) while 36% (18 patients) in group B which was statistically significant (p =0.0001). Severity of pain was more in group A which was statistically significant in comparison to group B (p=0.0001). The arm withdrawal during the injection of propofol was found more in Group A than Group B, 24% vs 0% (p=0.0002). Recall of pain after 4 hours postoperatively was found in 5 patients of Group A (10%) and 3 patients of Group B (6%) which came out to be statistically insignificant (p=0.715). There was no significant difference between  groups regarding heart rate, mean arterial pressure, respiratory rate and arterial hemoglobin oxygenation at all assessed times (p > 0.05) intraoperatively.Conclusion: This study clearly shows the incidence and severity of pain on intravenous administration in nanoemulsion Propofol is significantly less. However, amnestic effect was equally present in both the groups.